Synthesis of Carbon Dots From Empty Fruit Bunch Biochar an Acid-Free Hydrothermal Method - Marpongahtun Marpongahtun; Rufina Pramudita; Saharman Gea; Amru Daulay (Elkawnie: Journal of Islamic Science and Technology, 2023)
Abstract: Carbon dots have gained much interest due to their outstanding optical and electrical properties, making them useful for a wide range of applications. Here Empty fruit bunch (EFB) biochar was used as a carbon source in a straightforward, environmentally friendly, and reproducible hydrothermal method for producing carbon quantum dots. In this study, the role of the hydrothermal process was seen and studied by comparing the shape and fluorescence. Exciting results from HRTEM show that the carbon quantum dots in the sample are 4 nm in size. The obtained CD emits bright blue luminescence, and the absorption peak of the carbon dots was observed in the UV region with maximum absorption at 205 nm and 322 nm. The light CD shows an intense sky blue color upon illumination by a UV-light source at 365 nm. The intensity of the photoluminescence (PL) spectra sharply increases with decreasing concentration of carbon dots. Meanwhile, the CD exhibited excitation-dependence, photo-stability, and well dispersibility. These results suggest that the present CD are potential applications in optoelectronics and imaging.Abstrak: Karbon dots telah menarik banyak perhatian karena sifat listrik dan optik yang luar biasa, sehingga dapat digunakan untuk berbagai aplikasi. Penelitian ini, menggunakan biochar tandan buah kosong (EFB) sebagai sumber karbon dengan metode hidrotermal yang ramah lingkungan untuk menghasilkan karbon dots. Hasil HR-TEM yang menarik menunjukkan bahwa sampel karbon dots berukuran 4 nm. Karbon dots yang diperoleh memancarkan sinar biru terang dan puncak serapan titik karbon diamati pada spektrofotometri Uv-Vis dengan serapan maksimum pada 205 nm dan 322 nm. Intensitas karbon dots menunjukkan warna biru langit di cahaya UV pada 365 nm. Intensitas spektroskopi luminesens meningkat tajam dengan menurunnya konsentrasi titik karbon. Sementara itu, karbon dots menunjukkan eksitasi, stabilitas, dan dispersibilitas baik. Hasil ini menunjukkan bahwa karbon dots dapat digunakan pada beberapa aplikasi seperti dalam optoelektronik dan pencitraan.